Year of the Rabbit [videorecording (Blu-Ray)] - Cecil, Kevin, 1969-; Riley, Andy; Berry, Matt, 1974- (All3Media, 2026)
Detective Inspector Rabbit, a dedicated, tough, thick, and oft-inebriated Victorian copper, sleuths his way across London with his two young partners: a doofy rookie and a brilliant Black policewoman no one ever believes.